2009
DOI: 10.1038/mp.2009.21
|View full text |Cite
|
Sign up to set email alerts
|

Association of DISC1 and TSNAX genes and affective disorders in the depression case–control (DeCC) and bipolar affective case–control (BACCS) studies

Abstract: The gene known as Disrupted-in-Schizophrenia-1, DISC1, was originally discovered in a large family, in which it also co-segregated with bipolar affective disorder (BD) and with major depressive disorder (MDD). The TSNAX (Translin-associated factor X) gene, located immediately upstream of DISC1, has also been suggested as a candidate gene in relation to psychiatric illness, as one transcript resulting from intergenic splicing encodes a novel TSNAX-DISC1 fusion protein. We explored the TSNAX-DISC1 gene region fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 27 publications
1
28
0
2
Order By: Relevance
“…Also, rs766288 was the almost same MAFs in both Japanese and Caucasians. Schosser et al (2009) reported that rs766288 was not associated with BP or MDD in the UK population. Although they selected only one SNP (rs766288) in TSNAX, their study was a case-control study using larger samples than our study (Schosser et al 2009).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Also, rs766288 was the almost same MAFs in both Japanese and Caucasians. Schosser et al (2009) reported that rs766288 was not associated with BP or MDD in the UK population. Although they selected only one SNP (rs766288) in TSNAX, their study was a case-control study using larger samples than our study (Schosser et al 2009).…”
Section: Discussionmentioning
confidence: 96%
“…Schosser et al (2009) reported that rs766288 was not associated with BP or MDD in the UK population. Although they selected only one SNP (rs766288) in TSNAX, their study was a case-control study using larger samples than our study (Schosser et al 2009). Hennah et al haplotype transmission analysis showed that SNPs in intron 4 in TSNAX (rs1615344, rs1615409, and rs766288) was associated with schizophrenia.…”
Section: Discussionmentioning
confidence: 96%
“…Genotyping of the DeCC sample was performed using SNPlexÔ Genotyping System (PE Applied Biosystems, Foster City, CA) as described previously [Schosser et al, 2010]. One SNP, rs1394015 in ZNF80 could not be typed using SNPlexÔ and was genotyped using a Taqman Ò SNP genotyping platform (PE Applied Biosystems).…”
Section: Genotypingmentioning
confidence: 99%
“…The DeCC (Depression Case Control) sample consists of cases of recurrent depression fulfi lling DSM-IV and/or ICD-10 criteria of at least moderate severity ascertained from three UK clinical sites (London, Cardiff and Birmingham) (Schosser et al 2010). Subjects were identifi ed from psychiatric clinics, hospitals, general medical practices, and from volunteers responding to media advertisements.…”
Section: Samplesmentioning
confidence: 99%